Exploring Directions for Professional Learning to Enhance Behavior Screening Within a Comprehensive, Integrated, Three-Tiered Model of Prevention. (October 2022) - Briesch, Amy M.; Chafouleas, Sandra M.; Iovino, Emily A.; Abdulkerim, Noora; Sherod, Rebecca L.; Oakes, Wendy Peia; Lane, Kathleen Lynne; Common, Eric Alan; Royer, David J.; Buckman, Mark
Integration of multitiered academic, behavioral, and social-emotional efforts, such as the implementation of a Comprehensive, Integrated, Three-Tiered (Ci3T) model of prevention, is critical for supporting student development across domains of functioning. In particular, universal behavior screening has been shown to predict outcomes across these domains and as such is foundational to integrated systems. Thus, districts and schools are committed to continuing to learn how to implement behavior screening effectively and efficiently. As such, the purpose of this first qualitative study of systematic screening for behavior was to explore perspectives on benefits, challenges, and opportunities in behavior screening as gathered from members of school- and district-based leadership teams who were currently implementing Ci3T. Both individual interviews and focus groups were conducted, and thematic analysis was employed to identify themes that could be used to enhance the implementation and use of behavior screening. Ci3T Leadership Team members indicated knowledge about behavior screening procedures and relayed challenges with respect to using behavior screening data. Taken together, a need emerged for broader professional learning for all school staff members around increasing knowledge and use of behavior screening data. We discuss limitations and directions for future research.